CONTEXTUAL FACTORS OF POSYANDU ON CADRE PERFORMANCE IN PROVIDING MATERNAL AND CHILD HEALTH SERVICE IN SURAKARTA, CENTRAL JAVA - Pangestuti, Restu; Dewi, Yulia Lanti Retno; Sulaeman, Endang Sutisna (Journal of Maternal and Child Health, 2020)
Background: Cadre performance is an indicator of the success of the Posyandu program in maternal and child health services. Individual and social factors can influence the performance of cadres in providing health services. The purpose of this study was to determine factors affecting cadre performance in Surakarta, Central Java.Subjects and Method: This was an analytic observational study with a cross sectional design. The study was conducted on 25 integrated health services (posyandu) in Surakarta, Central Java, from June to July 2019. A sample of 200 cadres was selected by simple random sampling. The dependent variable was cadre performance. The independent variables were age, marital status, education, work, tenure, training, knowledge, and information. The data were collected by questionnaire and analyzed by a multilevel logistic regression run on Stata 13.Results: Good cadre performance increased with age ?39 years (b = 1.70; 95% CI= 0.67 to 2.74; p= 0.035), education ?senior high school (b= 2.69; 95% CI= 1.10 to 4.28; p= 0.030), working at home (b= 1.87; 95% CI= 0.81 to 2.93; p= 0.024), tenure >3 years (b= 2.39; 95% CI= 1.21 to 3.56; p= 0.009), had trained (b= 1.94; 95% CI= 0.86 to 3.01; p= 0.021), married (b= 1.68; 95% CI= 0.75 to 2.60; p= 0.021), good knowledge (b= 2.17; 95% CI= 0.95 to 3.40; p= 0.023), and good information (b= 1.50; 95% CI= 0.36 to 2.63; p= 0.091). Posyandu had strong contextual effect on cadre performance with intraclass correlation (ICC)= 53.22%.Conclusion: Good cadre performance increases with age ?39 years, education ?senior high school, working at home, tenure >3 years, had trained, married, good knowledge, and good information. Posyandu has strong contextual effect on cadre performance.Keywords: work performance, maternal and child health, health services, cadreCorrespondence: Restu Pangestuti. Masters Program in Public Health, Universitas Sebelas Maret, JL. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: restupanges@gmail.com. Mobile: 085741405163 Journal of Maternal and Child Health (2020), 5(1): 28-36https://doi.org/10.26911/thejmch.2020.05.01.04